Augustin Calmet and the Construction of the Eighteenth-Century Vampire - Ciaran Craig (Central Europe, 2021)
This article examines the role played by Augustin Calmet, a Benedictine, in the construction of the vampire. In the eighteenth century, Calmet embarked upon a thorough examination of the evidence for the existence of reported vampires in the lands of Hungary, Moravia, Serbia, and Romania. In order to complete this task, Calmet would investigate numerous incidents of apparent vampirism as well as the particular qualities that define these claims. However, Calmet’s emphasis and focus upon these features of “vampirism” would assist in the creation of an archetypal vampire, which would endure for the next three centuries.